The experiences of adult patients involved in clinical teaching sessions conducted by health professionals in an academic hospital - Nxumalo, Mercedes Zanele (My University, 2014)
The purpose of this study was to describe the experiences and perceptions of adult patients in relation to their rights and their involvement in clinical teaching sessions in an academic hospital. A descriptive survey design was used. A structured questionnaire with both open and closed-ended questions was used to interview a systematic random sample of 218 hospitalised patients. Several strategies including a pilot study were implemented to ensure reliability and validity. Percentages and chisquare analysis were obtained by use of a Statistical Analysis System (SAS) Software Programme. Qualitative data was sorted into descriptive categories, to which numerical codes were assigned. A narrative text was written. The majority of patients had knowledge of their rights except for their right to autonomy. They reported that their rights were observed during clinical teaching except for their right to respect, health care and education and communication.Patients’ knowledge of their rights, especially their right to autonomy and education depended on their educational status. Similarly the extent to which patients perceived whether or not their rights were observed depended on their knowledge of their rights. Although patients had both positive and negative experiences during clinical teaching, they were generally positive about their involvement in health professional education. Patients also suggested strategies to increase their comfort during clinical teaching sessions.